THE AWARENESS OF PARENTS REGARDING THE IMPACT OF TECHNOLOGY ON THE HEALTHY LIVES OF THEIR CHILDREN - Aline Medianeira Gomes Correa; Adriana Dall'Asta Pereira; Dirce Stein Backes; Carla Lizandra de Lima Ferreira; Eduarda Signor; Marielle Kulakowski Obem (Universidade Federal do Paraná, 2015)
The goal of this study is to identify, through qualitative approach with descriptive content, parents awareness about technology impact on healthy lives of their children. Data was collected in two schools, located in the city of Santa Maria, state of Rio Grande do Sul, during the second semester in 2013, by doing fifteen semi-structured interviews. After analyzing the results, it was noticed that the impacttechnologies have on lives of children is clear and negative. It promotes isolation and sedentariness, besides, the interferance on the development of the child, that keeps from seeking other ways of amusement. In this context, the nursing department sees as its duty to guideparents to lead ahealhty lifestyle, and from then on, following as example to improve thehabits of their children. It must be observed the importance of multidisciplinary work, through partnerships that focus on estimulating the care about the health of the children.